Direitos humanos e cidadania em foco: percepções sobre a formação do policial militar da Paraíba - Brito, Francisco de Assis Toscano de (2005)
To approach the subject Right Human and Policy in only a proposal is sufficiently pertinent ahead of the related problems the violence that if finds gift in the Brazilian society in this beginning of century. Thus, one searchs with this research to verify as the official futures of Military Police of the Paraíba perceive the Human Rights and its applicability in its práxis daily. The methodology this study uses a qualitative boarding and carrying through an analysis of content of the perceptions of the pupils of the Course of Formation of Officers of the Military Policy of the Paraíba on its formation in Human Rights and Citizenship, the conceptions that guide its daily one and the implications in practical its. It presents the evolution of the conceptions on the human rights throughout history. It analyzes the formation of the pupil to the light of estimated of the law and the too much aspects that turn on the subject, approaching as if of the a construction of knowing them and of the abilities of the military policeman in human rights and as these must be applied to take care of to the necessities of the society. We conclude that the necessity of a permanent process of formation of the policeman exists, where theoretical and methodological references permanently are evaluated and reconstructed, therefore only one well sedimented theoretical recital is not enough, is necessary that the professionals of the security publish, either Militate Policy, Civilian or Federal lives deeply moments of reflection on its practical formation and its.